Acceptance of the international compensation regime for tanker oil pollution – And its implications for China. (November 2015) - Dong, Bingying; Zhu, Ling; Li, Kevin; Luo, Meifeng
Abstract: The international compensation regime for tanker oil pollution has been successful in providing adequate and prompt compensation to pollution victims in its member states. Nevertheless, the attitudes of different countries toward acceptance of this regime have varied considerably. This paper aims to explain three main factors in the acceptance of the regime, including: (1) The level of economic development; (2) the risk of exposure to tanker oil spills; and (3) the financial burden associated with adherence to the International Oil Pollution Compensation Fund (IOPC). Using both fuzzy-set Qualitative Comparative Analysis and an Ordered Probit model, this study found two patterns causing upper-middle and high income countries to have a high acceptance level: (a) Those facing a medium risk of oil spills and having a low financial burden; and (b) those facing a high risk of oil spills. The study reveals that, for a country with a high risk of exposure to tanker oil spills, such as China, with its improvement in economic status it is far better for it to join the IOPC Fund, so as to provide better protection both for potential pollution victims and for the marine environment. The results of this study can also be applied to other countries that are considering whether or not to accept the international compensation regime for tanker oil pollution. Highlights: Economic status, oil spill risks and financial burden are three major factors making for high acceptance. Their roles are analyzed using logical qualitative and statistical quantitative models. Wealthy states having high risk or medium risk and low financial burden have high acceptance. In keeping with its improved economic status, China should arrange better protection for its pollution victims.